37th Annual Hawaii International Conference on System Sciences, 2004. Proceedings of The 2004
DOI: 10.1109/hicss.2004.1265156
|View full text |Cite
|
Sign up to set email alerts
|

Trust in virtual teams: towards an integrative model of trust formation

Abstract: Traditional models of trust have seen trust as being created as a result of a long history of interaction, but recent studies of trust in virtual teams have shown the existence of high initial trust among team members. This paper proposes an integrated model of trust that encompasses both the traditional view of trust and the swift trust found in virtual teams. Based on the dual process theories of cognition, we argue that individuals form trust attitudes via three distinct routes at different stages of a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 39 publications
4
135
0
Order By: Relevance
“…One way to support distributed team members with the formation of trustworthiness is to provide opportunities for accumulating personal knowledge and task-relevant background information [21,26]. Feng claimed that, "developing artifacts to help people to identify others who are similar to themselves or who have similar experiences may be helpful for promoting empathic attitudes that build interpersonal trust" [14].…”
Section: A Template For Supporting Initial Trust 31 Support Of Initimentioning
confidence: 99%
See 1 more Smart Citation
“…One way to support distributed team members with the formation of trustworthiness is to provide opportunities for accumulating personal knowledge and task-relevant background information [21,26]. Feng claimed that, "developing artifacts to help people to identify others who are similar to themselves or who have similar experiences may be helpful for promoting empathic attitudes that build interpersonal trust" [14].…”
Section: A Template For Supporting Initial Trust 31 Support Of Initimentioning
confidence: 99%
“…According to multidimensional trust research, two dimensions of trust have been identified as important to organizations: cognitive trust and affective trust [30]. Specifically, "cognition-based trust results from deliberate assessment of each other's characteristics and the process of weighting benefits of trusting over risks, whereas affect-based trust involves one's emotional bonds and sincere concern for the well-being of the others" [21].…”
Section: Motivation 21 Understanding the Concept Of Trustmentioning
confidence: 99%
“…Previous research covers, for example, the meaning of social ties in virtual collaboration, transferring knowledge, or building social capital [6,9,12]. Moreover, the building of personal relationships via ICT has been broadly examinedfor example, in forming trust [24,25] -but there is an absence of research on actual social tie strengthening via ICT. Trust has an essential role in tie-strengthening, but it is only one of the many tiestrength components [13,14].…”
Section: Strengthening Ties Via Ictmentioning
confidence: 99%
“…Trust measures have been derived from information withholding (deceit) [21], agent reliability [22,23], agent opinion based on deceitful actions [16], compliance with virtual social norms [24], and compliance with an a priori set of trusted behaviors from a case study [25]. Models of trust range from beta probability distributions over agent reliability [16], to knowledge-based formulas for trust [25], to perception-specific process models for trust [24].…”
Section: B Models and Measures Of Trustmentioning
confidence: 99%